Differences by gender at twelve months in a brief intervention trial among Mexican-origin young adults in the emergency department. Issue 1 (2nd January 2017) - Bernstein, Judith; Bernstein, Edward; Hudson, Dantia; Belanoff, Candice; Cabral, Howard J.; Cherpitel, Cheryl J.; Bond, Jason; Ye, Yu; Woolard, Robert; Villalobos, Susana; Ramos, Rebeca
ABSTRACT: In this study, we investigate the role of gender in prevalence and consequences of binge drinking and brief intervention outcomes among Mexican-origin young adults aged 18–30 years at the U.S.-Mexico border. We conducted a secondary analysis, stratified by gender, from a randomized controlled trial of a brief motivational intervention in a hospital emergency department. Intervention effects for males included reductions in drinking frequency, binge drinking, and alcohol-related consequences. For females the intervention was associated with reduction in drinking frequency and binge drinking but did not have a significant effect on alcohol-related consequences. Results suggest a new direction for tailoring interventions to gender.